Strategies to Increase Employee Engagement Through Employee Empowerment and Self-Development Programs - Yulianah, Yulianah; Galuh Boga Kuswara; Deri Apriadi; Kania Laelawati; Asri Sundari (SEAN Institute, 2025)
This study aims to describe and analyze strategies for increasing employee engagement through employee empowerment and self-development programs. The research approach used was descriptive qualitative, with data collection techniques using in-depth interviews, observation, and documentation studies. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing according to the Miles and Huberman model. The results indicate that empowerment and self-development strategies have a significant influence on increasing employee engagement. By providing autonomy in decision-making, providing relevant training, and supporting career development, employees feel more valued and in control of their work. Furthermore, a supportive organizational culture and regular recognition have been shown to increase motivation and a sense of belonging to the organization. Although challenges remain, such as budget constraints, ineffective training methods, and difficulties in measuring success, the results of this study confirm that employee engagement can be significantly improved if organizations consistently implement empowerment and self-development strategies on an ongoing basis.